Analysis of Post-Tonsillectomy Pain in Patients Treated with Unipolar and Bipolar Diathermy, a Comparative Study - Arshid, Farah; Niazi, Saleem Asif; Abbasi, Tooba; Sara Arshad; Zahra Batool; Inshaal Khalid (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare 24-hours post-operative pain in tonsillectomy performed using unipolar versus bipolar diathermy. Study Design: Quasi-experimental study. Place and Duration of Study: Pak-Emirates Military Hospital, Rawalpindi Pakistan from Nov 2023 to Nov 2024. Methodology: Fifty-four patients who underwent tonsillectomy with unipolar (Group A) or bipolar (Group B) diathermy were included. After twenty-four hours of surgery, post-operative pain score and presence of mild, moderate and severe degree of pain were assessed and compared between Groups. Data was analyzed by statistical package for social sciences 22. Results: Median age was 22.00 (30.00 – 15.00) years. There were 35(64.81%) male and 19(35.19%) female patients. Median number of tonsillitis episodes in last one year was 10.00 (18.00 – 7.00) episodes. Median 24-hour post-operative pain VAS score was 6.00 (9.00 – 1.00) in Group-A while in Group-B it was 3.00 (7.00 – 1.00), (p = 0.014). In Group-A, frequency of mild pain was 8(29.63%), moderate pain 8(29.63%) and severe pain 11(40.74%) while in Group-B, frequency of mild pain was 16(59.26%), moderate pain 6(22.22%) and severe pain 5(18.52%), respectively; (p = 0.074). Conclusion: Bipolar diathermy significantly reduces the pain score after 24-hours of tonsillectomy in comparison to unipolar diathermy making it a significantly better operative modality.